A experiência da estereoscopia no audiovisual contemporâneo (2005-2012) - Cordebello, Pedro Dolosic (2013)
Stereoscopic three dimensional pictures has gained significant importance in the entertainment industry nowadays. 3-D movies are intended to bring back the audience to the theater, and the stereoscopic television is the technology which will bring such immersive experience in the home. However, to produce, transport and show high quality stereoscopic content many skills and technologies are involved. The aim of this work is to bring some of the newest technological achievements in this area to anyone interested, and to contribute to scientific production in this research field.